Insecticide treatment of virus sources and host plants reduces number of vectors and incidence of rice virus diseases under greenhouse conditions (2012)
This study determined the effects of insecticides (pymetrozine, lambda-cyhalothrin + thiamethoxam, thiamethoxam + chlorantraniliprole, and thiamethoxam) on the acquisition of Rice tungro virus (RTV), Rice grassy stunt virus (RGSV), and Rice ragged stunt virus (RRSV) on treated virus sources and the inoculation of treated 7 and 35 day-old rice plants by nymph and adult Nephotettix virescens and Nilaparvata lugens including the insect vectors’ survival, lifespan, and fecundity on treated plants. The thiamethoxam treatments with lambda-cyhalothrin significantly interfered with N. virescens’ acquisition and inoculation feedings, subsequently lowering the tungro incidence compared to the untreated control and other insecticide treatments. Very few N. virescens, nymph or adult, survived the acquisition feeding on treated virus sources and most that survived did not transmit the virus on untreated test plants. Similarly, the transmission rate of RGSV and RRSV after acquisition of N. lugens on insecticide-treated virus sources, especially those with a common active ingredient (a.i.) of thiamethoxam, was significantly lower than those that acquired the viruses from the untreated virus sources. The survival rates of RTV-viruliferous nymph and adult N. virescens and RGSV and RRSV-viruliferous adult N. lugens at 24 h after exposure on 7 and 35-day old plants treated with thiamethoxam-laden insecticides were lower than those exposed to pymetrozine and the untreated control. Significantly fewer and shorter lifespan of nymph and adult N. virescens and N. lugens were recorded on those exposed on plants treated with the four treatments with thiamethoxam than those on pymetrozine-treated and untreated plants. Generally, insect exposure time on treated plants at 1, 10, and 24 h post treatments did not cause significant differences in acquisition and inoculation rates. Thiamethoxam as single a.i. or in mixed compounds gave comparable results while pymetrozine provided the least effect in all parameters tested. Thiamethoxam, particularly mixed with lambda-cyhalothrin, could effectively reduce the number of N. virescens and N. lugens and limit the incidence of the three rice virus diseases.